2013
DOI: 10.1186/1472-6963-13-50
|View full text |Cite
|
Sign up to set email alerts
|

Training health care professionals in root cause analysis: a cross-sectional study of post-training experiences, benefits and attitudes

Abstract: BackgroundRoot cause analysis (RCA) originated in the manufacturing engineering sector but has been adapted for routine use in healthcare to investigate patient safety incidents and facilitate organizational learning. Despite the limitations of the RCA evidence base, healthcare authorities and decision makers in NHS Scotland – similar to those internationally - have invested heavily in developing training programmes to build local capacity and capability, and this is a cornerstone of many organizational polici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 15 publications
0
51
0
2
Order By: Relevance
“…(15) The educational process is another essential service for the qualification of nursing staff, in the sense that this adds knowledge and increases the feeling of emotional security of the professional, enabling him/her to perform his/her practice in a competent, independent and collaborative way, which consequently impacts the quality of care. (16) The organizational environment can strongly influence the ability of nurses to build and maintain a therapeutic relationship with patients. This contact provides clinical supervision and follow-up of the interventions made by the technical team and establishes a more direct relational care with patients.…”
Section: Discussionmentioning
confidence: 99%
“…(15) The educational process is another essential service for the qualification of nursing staff, in the sense that this adds knowledge and increases the feeling of emotional security of the professional, enabling him/her to perform his/her practice in a competent, independent and collaborative way, which consequently impacts the quality of care. (16) The organizational environment can strongly influence the ability of nurses to build and maintain a therapeutic relationship with patients. This contact provides clinical supervision and follow-up of the interventions made by the technical team and establishes a more direct relational care with patients.…”
Section: Discussionmentioning
confidence: 99%
“…This group can gain experience and will have opportunities to retain their skills in reviewing incidents, especially when a new tool such as SCOR is used. 22 It has been shown that the interprofessional team is instrumental in role modelling, learning from mistakes, and taking a non-punitive approach to adverse events; this in turn promotes improved engagement among the staff in the unit. 22,23 One of the limitations of our study was the small number of incidents reviewed by the team.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been shown that the interprofessional team is instrumental in role modelling, learning from mistakes, and taking a non-punitive approach to adverse events; this in turn promotes improved engagement among the staff in the unit. 22,23 One of the limitations of our study was the small number of incidents reviewed by the team. However, as a result of this short pilot project there is interest at our institution in adopting this program for use as the standard method for quality assurance review.…”
Section: Discussionmentioning
confidence: 99%
“…Popular frameworks include the conceptual model (Ochberg et al 2007) and root cause analysis (RCA) (Bowie et al 2013). Uberoi et al (2007) suggested that RCA is a tool to identify prevention strategies, a process that is part of the drive to build a safety custom and move away from a blame culture.…”
Section: Root Cause Analysismentioning
confidence: 99%
“…RCA has been defined by Bowie et al (2013) as a structured approach to the investigation of patient safety incidents that is commonly applied in modern health systems worldwide, particularly in acute settings. The goal of RCA is to find out what happened, why it occurred and how to prevent it happening again.…”
Section: Root Cause Analysismentioning
confidence: 99%